Analisis Balaghah: Penerapan Uslub Tauriyah Dan Husnu Al-Ta’lil Yang Terkandung Dalam Surah Al-Waqi’ah - Suri, Nursukma; Khairina, Nana (Institut Muslim Cendekia, 2025)
This study aims to analyze the application of Balāghah styles, specifically tauriyah and husnu al-ta‘līl, in Surah Al-Wāqi‘ah. These two rhetorical devices are part of classical Arabic linguistic aesthetics that function to enhance meaning, deepen the message, and provide an artistic effect in the expression of Qur’anic verses. The research employs a qualitative-descriptive method through library research by examining classical Balāghah texts, tafsīr works, and relevant linguistic sources. The results indicate that Surah Al-Wāqi‘ah contains several instances of tauriyah, in which a word carries both a near (literal) and far (intended) meaning, enriching the interpretive depth of the verses. Additionally, forms of husnu al-ta‘līl are also identified, serving to beautify the reasoning or explanation within the context of the descriptions of the Day of Judgment and the conditions of humankind thereafter. The analysis concludes that the use of these two Balāghah devices not only enhances the literary beauty of the surah but also strengthens its theological and spiritual messages.